PATHOPHYSIOLOGY IN CLUSTER HEADACHE: AN UPDATE - Wa Ode Intan Nur Octina; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2023)
Cluster headache (CH) is a rare and very painful primary headache syndrome, with an estimated population prevalence of 0.12%. This condition can be episodic (ECH), lasting from 7 days to a year. A consensus statement from the European Headache Federation defines refractory CCH as a CCH with at least three severe attacks per week, even though at least three consecutive trials of adequate preventive care have been tested and managed with both acute and preventive treatment. Inhaled oxygen and subcutaneous sumatriptan are the two most effective acute treatment options for people with CH. Several preventive medications are also available, and the most effective is verapamil. However, most of these agents are not supported by strong clinical evidence. In some patients, this option may be ineffective, particularly in those with chronic CH. Surgical procedures for chronic refractory forms of disorder should then be considered.